The early Christians in their own words - Arnold, Eberhard, 1883-1935; Bruderhof Communities (Farmington, PA Plough, 1997)
Includes bibliographical references and index.
A translation of : Die Ersten Christen nach dem Tode der Apostel, Eberhard Arnlod Verlag / Sannerz and Hochweg Verlag, Berlin, 1926
Keywords: Christian literature, early; Church history -- primitive and early church, ca. 30-600.